Pemisahan dan Identifikasi Isomer Tokotrienol dari Tokotrienol Rich Fraction (TRF) - Lodu, Widiyasri; karwur, ferry fredy (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Palm oil is the largest agricultural product produced by Indonesia. Palm oil contains a large group of vitaminE which are tocopherol and tocotrienol which have been widely reported their efficacy in inhibiting the growthand development of diseases such as antioxidants, anti-cancer, cholesterol inhibitors, prevent premature aging,and cardioprotective effects. This study aims to segregate and identify the intensity of each isomer ofTocotrienol Rich Fraction (TRF). Segregation and identification are done through using columnchromatography, UV-visible spectrophotometer, and HPLC. The spectral pattern of TRF shows the presenceof tocotrienol isomers at wavelengths of 292-298 nm. Five spectra patterns identified with the highest intensitywere demonstrated by the Î³-tocotrienol isomers at 10.86 min, Î´-tocotrienol at the minute of 9.36, Î±-tocotrienolat the minute of 12:42, Î±-tocopherol at 21.11 and Î±-T1 at 17.35 with 0 intensity.